Performance Analysis on the Effect of G.729, Speex and GSM Speech Codec on 802.11g Wireless Local Area Network over VoIP using Packet Jitter - Imran Edzereiq, Kamarudin; Syahrizal Azmir, Md Sharif; Tutut, Herawan (Science & Engineering Research Support society, 2013)
In this paper, three speech codecs; G.729 (8 kbps), Speex (8kbps) and GSM (13kbps) were tested together with several predetermined SNR value ranging from 10dB to 45dB with a sample of 8 second speech. VoIP QoS such as packet jitter is analyzed in order to make a comparison of speech quality of those three speech codecs in wireless LAN 802.11g environment. Result shows that at lower SNR, GSM achieve higher packet jitter than that G.729 and Speex. At higher SNR, GSM achieves lower packet jitter as compared than that G.729 and Speex.